FORMULASI KRIM ANTI-AGING EKSTRAK ETANOL DAUN JELATANG (Urtica dioica L.) DENGAN PENAMBAHAN SARI LIDAH BUAYA (Aloe vera) - Rialita Lifiani; Tampubolon, Manuppak Irianto; Br purba, Hana Ike Dameria; Oktaviana, Leni (Universitas Sari Mutiara Indonesia, 2021)
Urtica dioica L. or what is known as nettle is a perennial plant from the Urticaceae family. The leaves contain various medically important organic compounds and have antioxidant potential, including flavonoids. Antioxidants can be further utilized for the development of anti-aging in the form of topical dosage forms in the form of creams because of their easy use. This study aims to formulate and test the anti-aging effectiveness of nettle leaf ethanol extract cream preparations with the addition of aloe vera juice and to find out whether a cream containing ethanolic extract of nettle leaf (Urtica dioica L.) with the addition of aloe vera juice is able to provide an Anti-Aging effect on the skin. The method used was the experimental method. Nettle leaf was extracted by maceration using 96% ethanol solvent and concentrated with a rotary evaporator at 40°C, then the extract was made into cream preparations with a concentration variation of 0.2% (F1); 0.3% (F2); 0.4% (F3) and 0.5% (F4) with the addition of aloe vera juice with a constant concentration of 3% in each formula. As blank (F0), the cream base was used without the addition of extract. Evaluation of cream preparations included organoleptic test, homogeneity, emulsion type test, pH, stability test, viscosity, irritation, and anti-aging effectiveness test using a skin analyzer. Observations were made for 28 days by applying cream preparations behind the volunteers' ears. Results Nettle leaf ethanol extract with the addition of aloe vera extract can be formulated in a homogeneous cream dosage form, with a pH of 6.30 – 6.69, a viscosity of 16250-26750 cps, stable in storage for 28 days, and does not irritate the skin of volunteers. The conclusion obtained is that nettle leaf ethanol extract with the addition of aloe vera juice can be formulated in the form of a cream dosage form and a concentration of 0.5% shows the best anti-aging effectiveness.